2019
DOI: 10.1044/2018_jslhr-h-18-0125
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Learning and Memory in Early-Implanted, Prelingually Deaf Adolescent and Adult Cochlear Implant Users

Abstract: The purpose of this study was to investigate the information-processing strategies of early-implanted, prelingually deaf cochlear implant (CI) users with the California Verbal Learning Test-Second Edition (CVLT-II; Delis, Kramer, Kaplan, & Ober, 2000), a well-established normed measure of verbal learning and memory used in neuropsychological assessments of memory loss. Method: Verbal learning and memory skills were compared in 20 older adolescent and young adult prelingually deaf long-term early-implanted CI u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…These qualities likely contribute to the lower reference value for NH listeners, and also to the lower SRT estimate in our study population. The shortness and simplicity of the test is essential for testing children, since their speech perception in noise is still maturing [19,49], and children with hearing loss may have a shorter auditory memory span [50,51]. Likewise, these qualities might render the test the most reliable SIN measure in the elderly, since ageing and age-related cognitive decline affect the speech perception in noise independently of the hearing level [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…These qualities likely contribute to the lower reference value for NH listeners, and also to the lower SRT estimate in our study population. The shortness and simplicity of the test is essential for testing children, since their speech perception in noise is still maturing [19,49], and children with hearing loss may have a shorter auditory memory span [50,51]. Likewise, these qualities might render the test the most reliable SIN measure in the elderly, since ageing and age-related cognitive decline affect the speech perception in noise independently of the hearing level [52][53][54].…”
Section: Discussionmentioning
confidence: 99%
“…The remarkable success of the CI is largely attributable to the proper use of signal transduction technology to harness central auditory plasticity of the implantees [2]. While CI users can significantly benefit from the neuroplasticity driven by the CI-empowered learning experience in developing their auditory, linguistic, and cognitive skills [3][4][5][6][7][8][9], pitch perception poses a unique challenge for these individuals. A vast body of literature demonstrated that CI recipients show deficits in pitch-related perceptual tasks, including voice emotion perception [10][11][12], speech prosody recognition [13][14][15], music appreciation [16][17][18], and lexical tone perception [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Previous literature has examined cognitive performance in relation to hearing abilities for the MoCA (Dupuis et al, 2015;Ambert-Dahan et al, 2017;Lim and Loo, 2018; Significant correlation between each of the trials 1-4 with the ISDA measures except for trial 5 which did not meet significance with Bonferroni correction; α = 0.017. Hillyer et al, 2020;Parada et al, 2020;Shen et al, 2020;Utoomprurkporn et al, 2020) and CVLT-3 (Kramer et al, 2018;Moseley, 2018;Pisoni et al, 2018;Chandramouli et al, 2019), demonstrating that differences in cognitive abilities due to sensory impairments like HL should be taken into account during test administration. Our current findings present the first application of the ISDA to a population with HL.…”
Section: Discussionmentioning
confidence: 99%
“…Using the California Verbal Learning Test—Third Edition (CVLT-3; Delis et al, 2017 ), a neuropsychological assessment of verbal learning and delayed recall, Pisoni et al (2018) demonstrated more retrieval-induced forgetting of stimuli in delayed recall tasks in experienced CI users compared to those without HL. Additionally, CI users benefited more from semantically cued words than individuals without HL suggesting that semantic cueing allowed individuals with HL to access words that were encoded but not accessible to non-cued retrieval ( Chandramouli et al, 2019 ; Kronenberger and Pisoni, 2019 ). Taken together, the current literature suggest that an impaired retrieval mechanism may underlie delayed recall deficits in individuals with HL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation